2006
DOI: 10.1021/jp056785i
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadditions on Diamond (100) 2 × 1:  Observation of Lowered Electron Affinity due to Hydrocarbon Adsorption

Abstract: The adsorption of allyl alcohol, acrylic acid, and allyl chloride, as well as unsaturated organic molecules such as acetylene and 1,3 butadiene, on reconstructed diamond (100) 2 x 1 have been investigated using high-resolution electron energy loss (HREELS) spectroscopy and synchrotron radiation spectroscopy. The cycloadditions of these organic molecules produce chemically adsorbed adlayers with varying degree of coverages on the clean diamond. The organic adsorbed surface has a lowered electron affinity and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Figure 1 shows core‐level photoemission spectra of the C1s electrons collected at two different electron take‐off angles (using a photon energy of 350 eV) after the sep‐by‐step deposition of C 60 onto a bare diamond (100)‐2×1 surface. Figure 1 a shows that the C1s emission peaks attributed to the bulk and the surface dimer are observed at 284.8 and 283.9 eV, respectively 24. A new peak, attributed to C 60 , appears at 284.1 eV after evaporating 0.2 monolyers of C 60 onto the surface (see Figure 1 b).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Figure 1 shows core‐level photoemission spectra of the C1s electrons collected at two different electron take‐off angles (using a photon energy of 350 eV) after the sep‐by‐step deposition of C 60 onto a bare diamond (100)‐2×1 surface. Figure 1 a shows that the C1s emission peaks attributed to the bulk and the surface dimer are observed at 284.8 and 283.9 eV, respectively 24. A new peak, attributed to C 60 , appears at 284.1 eV after evaporating 0.2 monolyers of C 60 onto the surface (see Figure 1 b).…”
Section: Resultsmentioning
confidence: 94%
“…What is the electronic structure of such an interface? In a previous study, we investigated the cycloaddition of a series of molecules, such as acetylene, allyl organics, and 1,3‐butadiene,24 on reconstructed diamond C(100)‐2×1. We found that conjugated molecules, such as 1,3‐butadiene, have high sticking probability and thermal stability on diamond 24–26.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface product was found to be stable up to approximately 1,000 K [59,60]. 1,3-Butadiene attains high coverage as well as forms a thermally stable adlayer on reconstructed diamond (100)-2 × 1 surface due to its ability to undergo [4+2] cycloaddition [61].…”
Section: [4+2] Cycloadditions On Surfacementioning
confidence: 99%
“…Indeed, we have previously observed the lowering of electron affinities on CA C H T U N G T R E N N U N G (100) 2 1 following hydrocarbon adsorption. [12,13] Several factors, such as the coverage of these hydrocarbons on diamond, as well as the geometrical orientation of the CÀH dipoles on these adsorbed species, may produce different effects on the surface electronic properties of the diamond. In order to investigate the roles of these factors, we carry out sticking probability studies to assess the reactivity of the clean diamond surface towards allyl organics such as acetylene and butadiene.…”
Section: Introductionmentioning
confidence: 99%